Homosexuality and Christian faith: questions of conscience for the churches (Fortress Press, 1999)
"Ideal for individual or group use, this unique resource presents short pieces from some of the nation's most preeminent church leaders - women and men, Protestant and Catholic, mainline and evangelical - who address fundamental moral imperatives about homosexuality. Through personal testimony, factual clarification, and moral suasion, they invite the reader to open his or her heart to the Spirit, to Gospel values, and to full acceptance of gay and lesbian persons in the "family of God.""--BOOK JACKET.
Introduction. More light from the Spirit on sexuality / James A. Forbes Jr. , A belated justice : reflections on an unpaid debt / Donald W. Shriver Jr. , Thoughts from the Weekend of the Quilt / Carole Shields , One family's story / Paul Wennes Egertson , Homosexuality and the Bible / Walter Wink , Biblical fidelity and sexual orientation : why the first matters, why the second doesn't / Ken Sehested , Homosexualities / Morton Kelsey and Barbara Kelsey , Accepting what cannot be changed / David G. Myers , Homosexuality : a word not written / Maria Harris and Gabriel Moran , Exploring the morality of homosexuality / Lewis B. Smedes , Where the Gospel leads us / Richard Rohr , Being Christian about homosexuality / John B. Cobb Jr. , In God's house there are many closets / Peggy Campolo , Liberty to the captives and good tidings to the afflicted / William Sloane Coffin , The challenge of nonconformity / Elise Boulding , Baptism, bread, and bonds : church rites for gay and lesbian Christians / Ignacio Castuera , Same-gender covenants / M. Mahan Siler Jr.